2018
DOI: 10.6004/jnccn.2018.7009
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous Medulloblastoma in a Child With Successfully Treated Neuroblastoma: Case Report and Novel Findings of DNA Sequencing

Abstract: Metachronous neoplasms have rarely been reported in patients with neuroblastoma. This report presents the clinical case of a 23-month-old child who was diagnosed with an anaplastic medulloblastoma 5 months after completing treatment for stage IV neuroblastoma. The patient was treated with complete surgical resection and adjuvant chemoradiation followed by maintenance chemotherapy at an outside institution and came to our institution for further management. A pathologic diagnosis and review of both the supraren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Naba et al reported SNED1 as characteristic protein of highly metastatic in mammary carcinoma, and the overexpression of SNED1 was associated with poor outcome for patients with ER−/PR− breast cancer [23]. The homozygous deletions of SNED1 might be involved in tumor metastasis of NB [24], while DNA methylation change of SNED1 was associated with the clinical course of NB [25]. However, the mechanisms of SNED1 involved in invasive phenotype remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Naba et al reported SNED1 as characteristic protein of highly metastatic in mammary carcinoma, and the overexpression of SNED1 was associated with poor outcome for patients with ER−/PR− breast cancer [23]. The homozygous deletions of SNED1 might be involved in tumor metastasis of NB [24], while DNA methylation change of SNED1 was associated with the clinical course of NB [25]. However, the mechanisms of SNED1 involved in invasive phenotype remains unclear.…”
Section: Discussionmentioning
confidence: 99%